Digital Transformation Model Of Sharia Financial Information Systems In Increasing Gen Z's Interest In Conducting Transactions At Sharia Banks - Munawaroh Munawaroh; Rizqy Fadhlina Putri; Melisa Zuhriani Hasibuan; Riyan Pradesyah (Yayasan Rahmat Islamiyah, 2026)
The digital transformation of the Islamic financial information system is a strategic need in the midst of rapid technological developments and changes in consumer behavior, especially generation Z. Islamic banks face the challenge of low interest in generation Z in making transactions, one of which is due to the limited ease of use and optimization of digital information systems. This study aims to analyze the influence of the digital transformation of the Islamic financial information system and ease of use on the interest of Generation Z transactions in Islamic banks. The research uses a quantitative approach with a survey method on generation Z in Medan City. Data analysis was carried out using Partial Least Squares– Structural Equation Modeling (PLS-SEM) through the SmartPLS application. The results of the study show that ease of use has a positive and significant effect on the interest of Generation Z transactions, while the quality of digital financial information does not have a significant effect. However, simultaneously the two variables are able to explain most of the variation in transaction interests. These findings confirm that the success of Islamic bank digital transformation in attracting the interest of generation Z is determined more by the ease of use of the system than the quality of information alone. This research is expected to be a strategic reference for the development of an Islamic financial information system that is more adaptive to the needs of the younger generation.